La comunicación pedagógica y el logro de aprendizajes significativos en los estudiantes de bachillerato del colegio Beatriz Cueva de Ayora, periodo lectivo 2013 – 2014 - Balseca Avila, Alexandra Mercedes (2014)
For the present investigation was stated objective: To analyze the pedagogical communication used by teachers in achieving meaningful learning in high school students from Beatriz Cueva de Ayora, this is a descriptive study methods were used: scientific, analytic-synthetic inductive - deductive. A survey and inventory of communication problems was applied to a sample of 1300 high school students. The results, 33 % of those surveyed indicate that the teacher has developed empathic ability and pedagogical communication strategy, 31% of students indicated that teachers in the classroom promote strategies for achieving meaningful learning through group work and the criteria for success at work. We conclude that most teachers have developed the skill of empathy as pedagogical communication strategy and setting the achievement of significant learning through group work encouraging success.